Establishment of gender management in the management sphere - Aksonova, Oleksandra; Maslova, Yuliia (Journal of Education, Health and Sport, 2021)
The concept of gender and gender management is considered in the article. The main aspects of gender management in the management sphere are singled out. The specifics of management of men-leaders and women-leaders are considered.